Titanic Struggle: Memory, Heritage and Shipyard Deindustrialization in Belfast. (25th February 2019) - Hodson, Pete
Abstract: Titanic Quarter has emerged as Belfast's premier tourist destination in recent years. This article examines ongoing regeneration efforts alongside the rundown of Harland & Wolff shipyard, which formerly occupied the Titanic Quarter site, and the delicate politics of Northern Ireland peacebuilding. East Belfast oral histories complement recently released state papers to analyze the intentions (and perceptions) of Titanic-themed urban transformation. The connected processes of deindustrialization, regeneration and industrial heritage are unpacked to better understand the cultural erasure and economic marginalization that can afflict displaced workers and communities. Lived social experiences have been largely ignored in heritage interpretations at Titanic Quarter in favour of non-contentious narratives serving the aims of state and corporate actors. Ultimately, the article questions whether attempts to create neutral 'heritage memory' tackles underlying divisions in post-conflict Northern Ireland.